A theory of the bargaining process - Cross, John C. (American Economic Review, 1965)
Offers a precise analysis of bargaining by means of a positive theory based on familiar economic concepts. Use of Nash theory; Components and the dynamic nature of bargaining process; Three conditions needed to satisfy the outcome of bargaining process; Analysis of the dynamic process of disagreement-concession-agreement; Fixed cost of bargaining; Nash condition of symmetry on the bargaining situation. (From Ebsco)